2008
DOI: 10.1074/jbc.m801363200
|View full text |Cite
|
Sign up to set email alerts
|

Redox Regulation of Epithelial Sodium Channels Examined in Alveolar Type 1 and 2 Cells Patch-clamped in Lung Slice Tissue

Abstract: The alveolar surface of the lung is lined by alveolar type 1 (AT1) and type 2 (AT2) cells. Using single channel patch clamp analysis in lung slice preparations, we are able to uniquely study AT1 and AT2 cells separately from intact lung. We report for the first time the Na

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
69
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(75 citation statements)
references
References 33 publications
5
69
0
1
Order By: Relevance
“…Both channels are activated by cyclic adenosine monophosphate and inhibited by amiloride. These findings are consistent with previous reports on the presence of various types of amiloride-sensitive Na 1 channels in alveolar epithelial cells both ex vivo and in vitro (35)(36)(37)(38)(39). Highly selective channels are composed of a-ENaC, b-ENaC, and g-ENaC subunits, whereas nonselective channels consist mainly of a-ENaC (37).…”
Section: Discussionsupporting
confidence: 82%
“…Both channels are activated by cyclic adenosine monophosphate and inhibited by amiloride. These findings are consistent with previous reports on the presence of various types of amiloride-sensitive Na 1 channels in alveolar epithelial cells both ex vivo and in vitro (35)(36)(37)(38)(39). Highly selective channels are composed of a-ENaC, b-ENaC, and g-ENaC subunits, whereas nonselective channels consist mainly of a-ENaC (37).…”
Section: Discussionsupporting
confidence: 82%
“…A representative trace using this experimental approach ( Figure 3F) shows the closing and opening of a 0.25 pA channel at a slightly depolarizing potential of 210 mV (2Vp). In the same cell-attached patch recording, application of TEMPO to the cell bath decreased ENaC activity, as we have reported previously (10,15), and subsequent treatment with CSE abrogated channel activity by 6 minutes. The presence of TEMPO, compared with the same time course of drug action observed in Figures 2 and 3 (performed in T1 and T2 cells, respectively), also decreased channel activity after more than 6 minutes of CSE exposure in T2 cells.…”
Section: Cse Increases Epithelial Sodium Channel Activity Via Oxidantsupporting
confidence: 54%
“…Alveolar type 1 (T1) and type 2 (T2) cells comprise the alveolar epithelium where gas exchange occurs. We have recently shown that both cell types express functional HSC and NSC channels and that both cell types play an important role in lung fluid homeostasis (10)(11)(12). Although one of the major problems associated with emphysema can be attributed to loss of T1 and T2 cells, we hypothesize that, similar to airway cells, cigarette smoke extract (CSE) can alter ion transport processes in the distal lung and lead to COPD.…”
mentioning
confidence: 99%
“…Rat primary alveolar T2 cells were isolated using a previously published protocol (20). Briefly, the lungs were perfused with phosphate-buffered saline (PBS) via the pulmonary artery and then extracted en bloc.…”
Section: Animalsmentioning
confidence: 99%
“…Lung slice preparation was performed as previously described (13,14,16,20,21) to access alveolar type 1 cells for patch analysis. Briefly, lungs were perfused via the pulmonary artery with 75 ml of PBS.…”
Section: Animalsmentioning
confidence: 99%